Flexible InGaZnO TFT devices obtained via humid-UV irradiation with an aqueous-fluoroalcoholic precursor. (1st November 2016) - Ogura, Shintaro; Cheong, Heajeong; Uemura, Sei; Ushijima, Hirobumi; Fukuda, Nobuko
Abstract: We designed an aqueous-fluoroalcoholic InGaZnO precursor for obtaining thin-film transistors (TFTs) on a flexible plastic film by spin-coating and low-temperature annealing processes without inert gas conditions. The precursor shows a low surface tension (23.7 mN m −1 ), which is advantageous for homogeneous coating onto plastic film. Thermal analysis of the precursor indicates formation of metal oxides at less than 300 °C. InGaZnO TFTs were obtained from the precursor by annealing at 300 °C via UV irradiation under humid atmosphere on a transparent polyimide film as well as on a p–Si substrate. The bottom-gate top-contact TFTs on the p–Si show 5.1 cm 2 V −1 s −1 of the average saturation mobility. The top-gate top-contact TFTs on the transparent polyimide film drive with 0.99 cm 2 V −1 s −1 of the average saturation mobility. The transparent polyimide film maintains flexibility even after humid-UV irradiation and annealing processes. The InGaZnO TFTs on the transparent polyimide film show more than 80% transmittance in the visible light region between 400 and 780 nm.